The Effects of Tensioning of the Anterior Cruciate Ligament Graft on Healing after Soft Tissue Reconstruction - Ma, Richard; Schaer, Michael; Chen, Tina; Nguyen, Joseph; Voigt, Clifford; Deng, Xiang-Hua; Rodeo, Scott A. (The Journal of Knee Surgery, 2019)
The purpose of this study is to determine the effect of the magnitude of static mechanical tension on the anterior cruciate ligament (ACL) graft at the time of surgery on healing within the graft tunnels. Ninety male rats underwent unilateral ACL resection followed by reconstruction with a soft tissue tendon autograft. The ACL graft mechanical environment was modulated by different ACL graft pretension levels at the time of surgery (no pretension: 0N; moderate tension: 5N; over tension: 10N). External fixators were used to eliminate graft and joint motion during cage activity. Graft–tunnel healing was assessed at 3- and 6-week postoperatively, and articular joint surfaces were assessed at 9 weeks. Our results demonstrate that the ACL graft–tunnel healing was sensitive to different static graft pretension levels as demonstrated by different load-to-failure and stiffness properties among the different pretension levels. Pretensioning the graft to 5N (7–8% of the rat ACL ultimate load to failure) resulted in the best graft–tunnel healing as shown by higher graft–tunnel failure load and stiffness. Higher bone volume fraction was also seen in the 5N group relative to other pretension levels. Histological analysis of the graft–tunnel interface revealed differences in cellularity of the ACL graft between the 5N group and the other two groups. Furthermore, the highest graft pretension level (10N) resulted in loss of proteoglycan content among articular joint surfaces. In conclusion, we found that ACL graft–tunnel healing is sensitive to the magnitude of graft pretension at the time of surgery in a preclinical model of ACL reconstruction with joint immobilization. The combination of high-graft tension and immobilization is also deleterious for the articular surface. Further study is necessary to understand the interaction between the magnitude of graft tensioning and joint motion.
Keywords: anterior cruciate ligament healing; graft healing; graft pretension; bone tunnel healing; anterior cruciate ligament